2011
DOI: 10.1346/ccmn.2011.0590506
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Textural Evolution Study of Zerovalent Iron/Montmorillonite Nanosized Heterostructures Under Various Iron Loadings

Abstract: Abstract-Heterostructures formed by nanoparticles hybridized with porous hosts are of great potential in many practical applications such as catalysis, adsorption, and environmental remediation, based on their intrinsic properties. The objectives of this study were to synthesize zerovalent iron nanoparticles/ montmorillonite heterostructures and to investigate their textural evolution under different Fe loadings. Iron nanoparticles were hybridized with montmorillonite by impregnation of montmorillonite by ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…NZVI/montmorillonite heterostructures were synthesized and their textural evolution under different Fe loadings was investigated. 104 The hybridized Fe nanoparticles were well dispersed on the montmorillonite surface, size adjustable, and resistant to oxidation under the protection of native Fe-oxide shells. It was revealed that as the Fe loadings increased, the total pore and mesopore volumes remained almost unchanged but the total, micropore and external surface areas as well as the micropore volume decreased and the average pore diameter increased.…”
Section: Coated and Supported Iron Nanoparticlesmentioning
confidence: 99%
“…NZVI/montmorillonite heterostructures were synthesized and their textural evolution under different Fe loadings was investigated. 104 The hybridized Fe nanoparticles were well dispersed on the montmorillonite surface, size adjustable, and resistant to oxidation under the protection of native Fe-oxide shells. It was revealed that as the Fe loadings increased, the total pore and mesopore volumes remained almost unchanged but the total, micropore and external surface areas as well as the micropore volume decreased and the average pore diameter increased.…”
Section: Coated and Supported Iron Nanoparticlesmentioning
confidence: 99%
“…Their adsorption capacity resulted from a relatively high surface area and a net negative charge on their structure, which attracted specially cations. On the other side, the presence of magnetite provided the advantage to the material be removed from the medium by a simple magnetic field [87].…”
Section: Applications In Azo and Antraquinonic Dyes Removalmentioning
confidence: 99%